Number Conceptualisation among Lebanese Micro-Business Owners who Engage in Orally-Based Versus Paper-Based Numeracy Practices - Zebian, Samar (2008)
The study of everyday numeric thinking in adults directs our attention to several aspects of number cognition that have received almost no attention in the experimental cognitive science literature, namely the influences of socially situated artifact use on numeric processing. The current studies explore numeral recognition and conceptualisation processes in business people who engage in different types of numeracy practices; orally based numeracy practices which involve very little use of written records compared to paper-based numeracy practices. Ethnographic observations of Lebanese business people were conducted to gain a detailed understanding of the socio-cognitive demands in orally-based paperless and paper-based business settings. These observations were in turn used to design experimental reaction time studies which investigated currency based numeral recognition and conceptualisation processes. The results of the numeral recognition and priming studies clearly illustrate that the use of artifacts in everyday numeracy practices influences numeral recognition and conceptualisation in a way that suggests tight linkages between the visio-spatial processes involve in recognizing numerals embedded in cultural artifacts and the semantically based processes involved in the conception of these numerals. The relevance of the current findings for the main models of adult numeric cognition and for research on everyday numeracy will be discussed